First Evidence of Retrospective Findings of Microplastics in Harbour Porpoises (Phocoena phocoena) From German Waters - Philipp, Carolin; Unger, Bianca; Ehlers, Sonja M.; Koop, Jochen H. E.; Siebert, Ursula (Frontiers in Marine Science, 2021)
Microplastic ingestion by lower trophic level organisms is well known, whereas information on microplastic ingestion, egestion and accumulation by top predators such as cetaceans is still lacking. This study investigates microplastics in intestinal samples from harbour porpoises (Phocoena phocoena) found along the coastline of Schleswig-Holstein (Germany) between 2014 and 2018. Out of 30 individuals found along the North Sea (NS) and the Baltic Sea (BS) coast, 28 specimens contained microplastic. This study found a relationship between the nutritional status of cetaceans and the amount of found microplastics. Harbour porpoises with a good or moderate nutritional status contained a higher number of microplastics, when compared with specimens in a poor nutritional status. In addition, when individuals died accidently due to suspected bycatch in gillnets, where a feeding event is highly assumed or a pharyngeal entrapment happened, the microplastic burden was higher. In total, 401 microplastics (≥100 μm), including 202 fibres and 199 fragments were found. Intestines of the specimens of the BS contained more microplastics than the ones from the NS. Differences in the share of fibres could be revealed: for BS fibres constituted 51.44% and for NS, fibres constituted 47.97%. The polymers polyester, polyethylene, polypropylene, polyamide, acrylic (with nitrile component) and an acrylic/alkyd paint chip (with styrene and kaolin components) were identified. This is the first study investigating the occurrence of microplastics in harbour porpoises from German waters and will, thus, provide valuable information on the actual burden of microplastics in cetaceans from the North and Baltic Seas.